Overload of the Temporomandibular Joints Accumulates γδ T Cells in a Mouse Model of Rheumatoid Arthritis: A Morphological and Histological Evaluation - Nagai, Kohei; Ishii, Takenobu; Ohno, Tatsukuni; Nishii, Yasushi (Frontiers in Immunology, 2022)
Recently, it has been reported that γδ T cells are associated with the pathology of rheumatoid arthritis (RA). However, there are many uncertainties about their relationship. In this study, we investigated the morphological and histological properties of peripheral as well as temporomandibular joints (TMJ) in a mouse model of rheumatoid arthritis with and without exposure to mechanical strain on the TMJ. Collagen antibody-induced arthritis (CAIA) was induced by administering collagen type II antibody and lipopolysaccharide to male DBA/1JNCrlj mice at 9−12 weeks of age, and mechanical stress (MS) was applied to the mandibular condyle. After 14 days, 3D morphological evaluation by micro-CT, histological staining (Hematoxylin Eosin, Safranin O, and Tartrate-Resistant Acid Phosphatase staining), and immunohistochemical staining (ADAMTS-5 antibody, CD3 antibody, CD45 antibody, RORγt antibody, γδ T cell receptor antibody) were performed. The lower jawbone was collected. The mandibular condyle showed a rough change in the surface of the mandibular condyle based on three-dimensional analysis by micro-CT imaging. Histological examination revealed bone and cartilage destruction, such as a decrease in chondrocyte layer width and an increase in the number of osteoclasts in the mandibular condyle. Then, immune-histological staining revealed accumulation of T and γδ T cells in the subchondral bone. The temporomandibular joint is less sensitive to the onset of RA, but it has been suggested that it is exacerbated by mechanical stimulation. Additionally, the involvement of γδ T cells was suggested as the etiology of rheumatoid arthritis.